The Implementation of the Independent Curriculum Policy in Islamic Religious and Character Education: A Study of Educational Reform in Indonesia - Sarbini; Nurdiansah, Nano; Samaun, Siti Salina (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2025)
The implementation of the Independent Curriculum (Kurikulum Merdeka) in the subject of Islamic Religious and Character Education has recently been initiated across various educational institutions in Indonesia. However, empirical studies examining how this policy is enacted at the school level remain limited. Therefore, this study aims to analyze the stages of policy implementation related to the Independent Curriculum in the teaching of Islamic Religious and Character Education. This research employed a qualitative case study design, focusing on an elementary school selected as the research site. Data were collected through interviews, classroom observations, and documentation, and were analyzed using a thematic analysis approach. The findings indicate that the implementation process has progressed positively, demonstrated by teachers’ ability to develop teaching modules, understand and integrate the Pancasila Student Profile, design P5 project modules, conduct assessments, and initiate differentiated learning. Furthermore, the implementation is carried out through classroom learning and through the Pancasila Student Profile Strengthening Project (P5), which is conducted once each semester.The study concludes that the adoption of the Independent Curriculum in Islamic Religious and Character Education shows promising improvements in instructional practices. These results suggest the need for continued professional development and institutional support to strengthen effective curriculum implementation in Indonesian schools.